DINAMIKA SEDIMEN DAN POTENSI KERENTANAN AIRTANAH DARI PEMBANGUNAN PELABUHAN TANJUNG ADIKARTA KABUPATEN KULON PROGO - , MALICHAH KURNIA PRTIWI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The development of Tanjung Adikarta Harbor in Karangwuni and Glagah villages, Kulonprogo District has some physical potential impacts such as sediment dynamics resulting from the construction of breakwater in the form of Jetties around the estuary of Serang River and groundwater tapping to meet the needs of port activity which can lead to vulnerability if it does not pay attention to the availability. This study uses digitized on screen and maps overlay methods as well as time series aerial photographs to determine the dynamics of the sediment around the mouth of Serang River before and after Jetties constructed. The static method is used to calculate the quantity its groundwater, then the vulnerability of groundwater is calculated by finding the difference between the availability of groundwater in the aquifer with groundwater harbor needs contained in the Final Report of the Feasibility Study Development of the Port of Tanjung Adikarta. The aerial overlay photo in 1981 with the scale of 1: 30,000, 1997, scale 1: 10,000, 2001, scale 1: 20,000, scale 1: 25,000 in 1992, scale 1: 50,000 in 1993 showed that insignificant sediment dynamics did not occur around the mouth of Serang River which was characterized by the narrow sediment area change. However, in terms of its shoreline changes, accretion occurred from 1981 to 1992. The sediments in the west and east side of the mouth of Serang River experienced accretion in 1981 to 1992, and prone to abrasion from 1992 to 2006, as seen from the shoreline change and the wide of sediment area changes. At the time before and after Jetties building no significant changes happened in the pattern of sediment around the estuary of Serang River due to processes occurring in the estuary is dominated by hydrooceanographic factors. In 2006 the east of Jetty sediment area of which its width is relatively large compared to the area a few years earlier showed a slight accretion. While in the west side of Jetty sediments area did not experience significant narrowing (abrasion) compared to previous years. Water needs for the harbor, as much as 49,616,640 liters / year can be met by the surrounding aquifer in Karangwuni and Glagah villages because the total volume of the aquifer in both villages is 58,916,550,000 m3. However if the water plastering for port coupled with water needs for the residents with both total 233,944,560 liters / year, then the number still can be met by the available aquifers. The need for groundwater number 233 944 560 liters / year which is plastered for port and domestic population needs does not exceed the safe yield limit that is 2.07368 billion m3/year that means it does not pose a potential seawater intrusion in Karangwuni and Glagah villages.